Authorial positioning systems - Erin Twohig (Francosphères)
This article examines how Moroccan authors cite each other in their literary works and how, in doing so, they trace the contours and location of a Moroccan literary sphere in French. While we might expect this type of citation to seek to ‘decentre’ France or disrupt French literary hegemony, it instead serves to position and legitimize the role of the ‘engaged’ author between various literary traditions. In order to elucidate this function, the article first examines previous work on how Moroccan and Maghrebi authors cite each other, discussing the possible meanings of this practice and of the types of critical attention it has garnered. The novels of Abdelhak Serhane are then examined as a noteworthy example of Moroccan intertext. Serhane’s practice of directly evoking other Moroccan francophone authors’ work offers a new means to consider intertext: as a deliberate contribution to the diversity of storytelling, and as a way to highlight the long yet complicated tradition of the politically engaged Moroccan intellectual.